Time Management Training Reduces Work Procrastination of Cadres: Pelatihan Manajemen Waktu Turunkan Prokrastinasi Kerja Kader - Maulidyah, Rizky Alfina; Maryam, Effy Wardati (Universitas Muhammadiyah Sidoarjo, 2024)
The General background procrastination is a prevalent issue that affects productivity and efficiency in various settings, including work environments. Specific background this behavior can be particularly detrimental among individuals with multiple responsibilities, such as community cadres, who often struggle to manage their time effectively. Knowledge gap despite the recognition of time management as a crucial skill, there is limited research on its impact specifically among community cadres in reducing work procrastination. Aims this study aims to evaluate the effectiveness of time management training on the procrastination levels of cadres in a specific area. Results a quantitative experimental approach using a one-group pretest-posttest design was employed, involving 41 active cadres who underwent the training. the findings revealed a notable decrease in procrastination levels, with pretest scores averaging 66.000 and posttest scores averaging 65.000, indicating a positive shift after the intervention. Novelty this research contributes to existing literature by highlighting the potential of targeted time management training in addressing procrastination among community workers. Implications the outcomes suggest that implementing such training could enhance productivity and efficiency among cadres, advocating for broader applications of time management strategies in similar community-based settings to foster improved performance and commitment. Highlights: Effective time management training significantly reduces procrastination levels among cadres. Quantitative experimental approach utilized for measuring training impact. Findings advocate for broader applications of time management strategies in community settings. Keywords: Procrastination, Training, Cadres, Productivity, Research